STABILITAS MARSHALL DAN KETAHANAN DEFORMASI WARM MIX ASPHALT MENGGUNAKAN ADITIF ZYCOTHERM - I Gusti Ngurah Widyantara; Latif Budi Suparma; Imam Muthohar (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2018)
ABSTRACTWarm Mix Asphalt (WMA) is produced at mixing temperatures between 20°C-40°C lower than Hot Mix Asphalt (HMA). Zycotherm added ingredients is one of the additives used in Warm Mix Asphalt. This study aims to assess Marshall stability and resistance to deformation by using asphalt type AC 60/70 ex Shell and Zycotherm additives on warm asphalt mixtures. In this study, the test was carried out on a layer of (AC-WC) to four mixed variations ie HMA-0, WMA-1, WMA-2, WMA-3 with 0% Zycotherm content; 0.10%; 0.15% and 0.20%. Mixed performance is measured by Marshall and Wheel Tracking Machine (WTM) testing. Based on the result of Gyropac test, with Workability Index (WI) value approach, the mixing temperature and compaction of WMA-1, WMA-2 and WMA-3 mixture are respectively obtained temperature 130/120°C, 130/120°C and 140/130° C. The Marshall test, the stability value of all mixtures fulfilled the minimum specification requirement of 800 kg, with the greatest stability value obtained from WMA-1 mixture of 1325 kg with additive content of 0.10%. The results of the Wheel Tracking Machine (WTM) test, a mixture that has resistance to deformation is a mixture of WMA-1 has the smallest deformation value of 1.93 mm, the largest dynamic stability of 1400 traje / mm and the smallest deformation velocity of 0.030 mm / min. That the use of Zycotherm is suitable for use in AC-WC warm mixture, with the optimum value of Zycotherm 0,10%. The use of excessive Zycotherm content results in a poor AC-WC warm mixture performance.Keywords: Dynamic Stability, Marshall, Warm Mix, Wheel Tracking Machine, Zycotherm. ABSTRAKWarm Mix Asphalt (WMA) diproduksi pada suhu pencampuran antara 20°C-40°C lebih rendah daripada Hot Mix Asphalt (HMA). Bahan tambah Zycotherm merupakan salah satu aditif yang digunakan dalam Warm Mix Asphalt. Kajian ini bertujuan untuk mengkaji stabilitas Marshall dan ketahanan terhadap deformasi dengan menggunakan bahan perekat aspal jenis AC 60/70 ex Shell dan aditif Zycotherm pada campuran aspal hangat. Pada kajian ini, pengujian dilakukan pada lapis aus (AC-WC) terhadap empat variasi campuran yaitu HMA-0, WMA-1, WMA-2, WMA-3 dengan kadar Zycotherm 0%; 0,10%; 0,15% dan 0,20%. Kinerja campuran diukur berdasarkan pengujian Marshall dan Wheel Tracking Machine (WTM). Berdasarkan hasil pengujian Gyropac, dengan pendekatan nilai Workability Index (WI) diperoleh suhu pencampuran dan pemadatan campuran WMA-1, WMA-2 dan WMA-3 secara berurutan diperoleh suhu 130/120°C, 130/120°C dan 140/130°C. Pengujian Marshall diperoleh nilai stabilitas semua campuran memenuhi ketentuan spesifikasi yaitu minimum 800 kg, dengan nilai stabilitas terbesar diperoleh dari campuran WMA-1 sebesar 1325 kg dengan kadar aditif 0,10%. Hasil pengujian Wheel Tracking Machine (WTM), campuran yang memiliki ketahanan terhadap deformasi adalah campuran WMA-1 memiliki nilai deformasi yang paling kecil sebesar 1,93 mm, stabilitas dinamis terbesar sebesar 1400 lintasan/mm dan kecepatan deformasi terkecil sebesar 0,030 mm/menit. Bahwa penggunaan Zycotherm cocok digunakan pada campuran hangat AC-WC, dengan nilai optimum penggunaan Zycotherm sebanyak 0,10%. Penggunaan kadar Zycotherm yang berlebihan menghasilkan performa campuran hangat AC-WC yang kurang baik.Kata kunci: Stabilitas Dinamis, Marshall, Warm Mix, Whell Tracking Machine,  Zycotherm.